Probiotics, their action modality and the use of multi-omics in metamorphosis of commensal microbiota into target-based probiotics - Idrees, Maryam; Imran, Muhammad; Atiq, Naima; Zahra, Rabaab; Abid, Rameesha; Alreshidi, Mousa; Roberts, Tim; Abdelgadir, Abdelmuhsin; Tipu, Muhammad Khalid; Farid, Arshad; Olawale, Oluwaseyi Abraham; Ghazanfar, Shakira (Frontiers in Nutrition, 2022)
This review article addresses the strategic formulation of human probiotics and allows the reader to walk along the journey that metamorphoses commensal microbiota into target-based probiotics. It recapitulates what are probiotics, their history, and the main mechanisms through which probiotics exert beneficial effects on the host. It articulates how a given probiotic preparation could not be all-encompassing and how each probiotic strain has its unique repertoire of functional genes. It answers what criteria should be met to formulate probiotics intended for human use, and why certain probiotics meet ill-fate in pre-clinical and clinical trials? It communicates the reasons that taint the reputation of probiotics and cause discord between the industry, medical and scientific communities. It revisits the notion of host-adapted strains carrying niche-specific genetic modifications. Lastly, this paper emphasizes the strategic development of target-based probiotics using host-adapted microbial isolates with known molecular effectors that would serve as better candidates for bioprophylactic and biotherapeutic interventions in disease susceptible individuals.